Social service providers' perspectives on caring for structurally vulnerable hospital patients who use drugs: a qualitative study - Nicole D. Gehring; Kelsey A. Speed; Kathryn Dong; Bernie Pauly; Ginetta Salvalaggio; Elaine Hyshka (BMC, 2022)
Abstract Background People who use drugs and are structurally vulnerable (e.g., experiencing unstable and/or lack of housing) frequently access acute care. However, acute care systems and providers may not be able to effectively address social needs during hospitalization. Our objectives were to: 1) explore social service providers' perspectives on addressing social needs for this patient population; and 2) identify what possible strategies social service providers suggest for improving patient care. Methods We completed 18 semi-structured interviews with social service providers (e.g., social workers, transition coordinators, peer support workers) at a large, urban acute care hospital in Western Canada between August 8, 2018 and January 24, 2019. Interviews explored staff experiences providing social services to structurally vulnerable patients who use drugs, as well as continuity between hospital and community social services. We conducted latent content analysis and organized our findings in relation to the socioecological model. Results Tensions emerged on how participants viewed patient-level barriers to addressing social needs. Some providers blamed poor outcomes on perceived patient deficits, while others emphasized structural factors that impede patients' ability to secure social services. Within the hospital, some participants felt that acute care was not an appropriate location to address social needs, but most felt that hospitalization affords a unique opportunity to build relationships with structurally vulnerable patients. Participants described how a lack of housing and financial supports for people who use drugs in the community limited successful social service provision in acute care. They identified potential policy solutions, such as establishing housing supports that concurrently address medical, income, and substance use needs. Conclusions Broad policy changes are required to improve care for structurally vulnerable patients who use drugs, including: 1) ending acute care's ambivalence towards social services; 2) addressing multi-level gaps in housing and financial support; 3) implementing hospital-based Housing First teams; and, 4) offering sub-acute care with integrated substance use management.